Lactic Acid Bacteria and Bioactive Amines Identified during Manipueira Fermentation for Tucupi Production - Brenda de Nazaré do Carmo Brito; Renan Campos Chisté; Alessandra Santos Lopes; Maria Beatriz Abreu Gloria; Gilson Celso Albuquerque Chagas Junior; Rosinelson da Silva Pena (Microorganisms, 2022)
There is scarce information regarding lactic acid bacteria (LAB) and the production of biogenic amines during manipueira fermentation for tucupi. Thus, the objective of this study was to isolate and identify LAB, and to determine their impact on bioactive amine formation. Spontaneous fermentation of manipueira was carried out at laboratory scale and selected LAB colonies were isolated and identified by sequencing techniques and comparison with sequences from a virtual database. Only two LAB species of the genus Lactobacillus were identified during fermentation: Lactobacillus fermentum and Lactobacillus plantarum. L. fermentum was the predominant, whereas L. plantarum was only detected in manipueira prior to fermentation. Spermidine and putrescine were detected throughout fermentation, whereas histamine was produced at the final stage. There was positive correlation between LAB counts and putrescine and histamine levels, suggesting that the identified LAB are responsible for the synthesis of these amines during manipueira fermentation. Genetic assays are needed to verify whether the LAB identified have the genes responsible for decarboxylation of amino acids.